Diretrizes para melhorias na produção de estrutura de concreto visando à redução de perdas: estudo de caso - Neves, José Ricardo Gonçalves (Universidade do Vale do Rio dos Sinos, 2009)
Rapid urbanization and densification of urban territory cause the increase in the volume of buildings in large cities and their respective metropolitan areas. This condition, coupled with the constant incentives to finance the construction, motivates the housing market triggering agents in order to meet this growing demand. Construction companies, developers, professionals, research institutions, universities and other agents of the process, seek to meet the demands reviewing practices widely used in the works in order to become more competitive in the industry. In recent years, a large number of builders joined the program of improvements in order to achieve higher standards of performance. The Associação Brasileira de Cimento Portland (ABCP), through the Community Building*, develops programs Best Practices with entities teachings and construction companies. This research was carried out using as an object of study work in the Valley of the Bells of a construction company of this program, which has found in his works some distortions related to the use of unusual materials, more than the amount projected and budgeted. The overall objective was to propose guidelines for improvements in the production of concrete structures in order to reduce losses. For this purpose, the subprocess and the implementation of concrete structure, identified and classified the losses present in the process as well as losses resulting from implementation of the concrete structure, identifying its origins and consequences. The use of Information Technology and Communication Technology (ICT) with the tool Building Information Modeling (BIM) in this study, presented situations of design problems could be avoided with the use of resources and potential of BIM.
Keywords: Construção civil; Perdas; Gestão; Controle de projetos; TIC; BIM; Construction; Losses; Management; Project control; ICT; ACCNPQ::Engenharias::Engenharia Civil